Protein-energy malnutrition and micro-nutrient deficiencies: Possible culprits in susceptibility and severity of visceral leishmaniasis - B. M. Younis; A. M. Musa; A. M. Abdelraouf; W. S. E. Saeed; M. A. Saeed; M. A. Magzoub; A. A. Beshir; M. E. E. Elfaki; Elyazeed N. Suliman; M. A. Awad Eljeed; A. J. Suleiman; E. A. G. Khalil (Annals of Medical Science and Research)
Visceral leishmaniasis (VL) is a widespread highly morbid tropical infection. Protein-calorie and micro-nutrient deficiencies contribute to susceptibility and disease severity. This study aimed to delineate the effects of protein-calorie malnutrition, selenium (Se), zinc (Zn), and copper (Cu)] level derangements on immune responses in VL patients. Following informed consent, 77 sequential parasitologically confirmed VL patients and 112 apparently healthy controls were recruited. Weight for height Z-score (WHZ), albumin, Se, Zn, and Cu were markers for protein-calorie and micro-nutrient disturbances. Leishmanin skin test (LST), direct agglutination test (DAT), and IL-10/TNF-α/IFN-γ levels in supernatants of soluble Leishmania–antigen whole blood-stimulated samples were measured as indicators of immune responses. VL patients have significantly lower baseline WHZ levels compared to controls (−2.2 ± 1.1 and −1.4 ± 1.3, respectively, P = 0.0006). Albumin levels were similarly reduced (2.9 and 3.4 g/dL, P = 0.06). Patients had marginally significant lower Se levels compared to controls (57.6 ± 13.1 and 61.7 ± 13.4 µg/L, respectively, P = 0.04). Pretreatment Se levels were significantly lower compared to post-treatment ones (56.9 ± 13.1 and 65.2 ± 22.1 µg/dL, respectively, P = 0.02). Zn levels were significantly lower in patients compared to controls (36.2 ± 17.3 and 72.9 ± 12.5 µg/L, respectively, P = 0.0002). Cu levels were four-fold higher in patients compared to controls [median 336 and 73.5 µg/L, respectively P = 0.00001]. The Cu:Zn ratio was significantly higher in patients compared to controls (9.6 and 1.0, respectively, P = 0.0001). LST was non-reactive in all VL patients with DAT levels >6400. Pre- and post-VL treatment levels of IFN-γ and IL-10 levels were comparable in patients and controls. Pretreatment TNF-α levels were significantly higher compared to post-treatment ones (median: 64.1 and 36.7 pg/mL, respectively, P = 0.0002). Five per cent (6/112, 5.4%) of the healthy controls developed VL during follow-up, and 15.2% (17/112) developed subclinical infection with LST conversion in 14/17 (82.4%, mean induration of 8.5 ± 2.6 mm). Three (3/17, 17.6%) converted in DAT and LST. Low WHZ, Se, and Zn levels with high Cu/Cu: Zn ratios probably increase susceptibility to VL.